PEMBELAJARAN TARI KREASI PERAHU LAYAR UNTUK MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK TUNAGRAHITA PADA SKh AL KAUTSAR KOTA CILEGON - Niken Indah Cahyani; Dr. Joko Yuwono, M.Pd; Dedi Mulia, M.Pd (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2018)
AbstractThis research aims to know the condition of the motor (1) gross motoric conditions of children before being given treatment creative dance learning (2) gross motoric conditions of children when given treatment creative dance learning (3) gross motoric skills of children after being given dance learning treatment creation. This research is an experimental study with a one group pretest posttest design approach. Data collection techniques in this study used observations in the form of a checklist and documentation in the form of photographs. The data obtained were analyzed using descriptive statistics and displayed using graphs. The results of this study indicate that there is an increase in gross motoric students using dance learning sailboat creations. It can be seen that there is an increase in the value of the average pretest and also the posttest obtained by students. The results of the average value before being given the dance learning treatment of sailboat creations (pretets) obtained at 31, 24% then increased after being given sailboat creation (posttest) dance learning treatment of 72, 18%. This can indicate that the division of dance sailboat creations can improve the gross motoric abilities of mentally retarded children.